IEO Evaluation Report : The IMF and Social Protection. (Independent Evaluation Office Reports; Independent Evaluation Office Reports, 2017)
This paper analyzes that the IMF has moved beyond its traditional fiscal-centric approach to recognize that social protection can also be macro-critical for broader reasons including social and political stability concerns. Evaluating the IMF's involvement in social protection is complicated by the fact that there is no standard definition of social protection or of broader/overlapping terms such as social spending and social safeguards in (or outside) the IMF. In this evaluation, social protection is understood to include policies that provide benefits to vulnerable individuals or households. This evaluation found widespread IMF involvement in social protection across countries although the extent of engagement varied. In some cases, engagement was relatively deep, spanning different activities (bilateral surveillance, technical assistance, and/or programs) and involving detailed analysis of distributional impacts, discussion of policy options, active advocacy of social protection, and integration of social protection measures in program design and/or conditionality. This cross-country variation to some degree reflected an appropriate response to country-specific factors, in particular an assessment of whether social protection policy was macrocritical, and the availability of expertise from development partners or in the country itself.